The Effect of Tax Socialization, Ownership of Taxpayer Indication Number and Inspection Tax To Reception Tax Income People Personal on Office Service Tax Primary Makassar West - Syamsi Rohma (Golden Ratio of Taxation Studies, 2021)
The purpose of this study was to analyze the influence of tax socialization, ownership of the taxpayer identification number and tax audit on personal income tax receipts. The number of taxpayers from year to year is increasing increase. However, the increase in the number of taxpayers is not matched by tax revenues. This research examines level reception tax income people personal which registered in region KPP Primary Macassar West with use several independent variables, namely tax socialization, ownership of a taxpayer identification number, and tax audits. data that used in this research is the primary data obtained from the research location, namely through the distribution of questionnaires or questionnaire (list question to respondent). Sample consists from 98 respondent which is must tax people personal active as well as data secondary which obtained from KPP Primary Macassar West which relate tightly with study this. Data tested with use analysis regression linear double. Testing data use SPSS 20. Researcher also do test validity and reliability test for the questionnaire. Classic assumption test used is test multicollinearity, normality test, and test heteroscedasticity. To test the hypothesis, the researcher uses the coefficient of determination (R2), simultaneous test (F-test), and test partial (t-test). Based on the results of the analysis carried out, it is concluded that tax socialization, ownership number tree must tax and inspection tax influential positive and significant to reception tax income people personal on KPP Primary West Makassar.